Challenges in the Creation of the Curricula of the Faculty of Islamic Theology in Sarajevo and Their Implementation (1977–1992) - Kulenović, Azra (Context: Journal of Interdisciplinary Studies, 2024)
This paper analyses the creation of the first curricula of the Faculty of Islamic Theology in Sarajevo, and the challenges that arose during their implementation. This topic was previously addressed in the 2017 monograph Faculty of Islamic Studies University of Sarajevo 1977-2017, published for the university’s 40th anniversary. Although the paper uses the information presented in this publication, it goes a step further to examine the process of curriculum implementation, the issues inherent to this process, and the successful and less successful ways in which it dealt with these challenges.